2019
DOI: 10.3390/antibiotics8040243
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Antimicrobial Resistance among Veterinary Students and Their Personal Antibiotic Use Practices: A National Cross-Sectional Survey

Abstract: The challenge of antimicrobial resistance (AMR) is grave in developing countries. Antimicrobials are misused yet stakeholders’ contribution to antimicrobial stewardship is low. Veterinary students are future prescribers and their knowledge could influence progress in combating AMR; hence, there is a need to assess their knowledge, attitude, and awareness of AMR. A multi-institutional questionnaire was administered to undergraduates in Nigerian veterinary schools. It comprised demographics, own personal antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 32 publications
8
45
2
Order By: Relevance
“…Except for evidence that AHSPs are associated with farmers having prescriptions, we did not find consistent and significant associations between self-reported prudent use and withdrawal practices and frequency of seeking advice across the five types of AHSPs included in this study (i.e., government veterinarians, private veterinarians, extension officers, feed distributors, and agrovet employees). These findings are somewhat consistent with knowledge, attitudes, and practices studies of AHSPs that document variable understandings of antimicrobial stewardship and impacts on prudent use, and so suggest that seeking advice from these providers may not improve prudent practices on the farm [10,23,24]. Combined with these earlier findings, this study emphasizes the need for antimicrobial stewardship training programs to ensure high-quality advice is provided by AHSPs.…”
Section: Discussionsupporting
confidence: 82%
“…Except for evidence that AHSPs are associated with farmers having prescriptions, we did not find consistent and significant associations between self-reported prudent use and withdrawal practices and frequency of seeking advice across the five types of AHSPs included in this study (i.e., government veterinarians, private veterinarians, extension officers, feed distributors, and agrovet employees). These findings are somewhat consistent with knowledge, attitudes, and practices studies of AHSPs that document variable understandings of antimicrobial stewardship and impacts on prudent use, and so suggest that seeking advice from these providers may not improve prudent practices on the farm [10,23,24]. Combined with these earlier findings, this study emphasizes the need for antimicrobial stewardship training programs to ensure high-quality advice is provided by AHSPs.…”
Section: Discussionsupporting
confidence: 82%
“…In general, in this survey females were more represented than males. Moreover, the gender distribution of 67.6% of females (Table 1) in this study was similar to the one of veterinary students in Australia [75]. In addition, the gender distribution of surveyed veterinary students was similar at the University of Zagreb and the University of Novi Sad.…”
Section: Limitationssupporting
confidence: 74%
“…In Australia, one survey [39] has shown that more than 80% of veterinary students, while another study [74] has shown that more than 60% of them perceived that statement. Contrary, in Nigeria a very low percentage of veterinary students (13.1%) [75] and veterinarians (17.1%) [76] have heard about AMS, as well as only about 24% of pharmacy students in Saudi Arabia [77]. Having appropriate knowledge on AMS at the undergraduate level could insure AMS implementation in future work of veterinarians.…”
Section: Plos Onementioning
confidence: 99%
“…To summarize the obtained data, the demographic characteristics of respondents were subjected to descriptive statistics (frequency and proportions). To assess knowledge, attitude, and perception levels of respondents, a numeric scoring pattern was used, and outcome (dependent) variables-knowledge, attitude, and perception-were computed [19]. These outcome variables were further categorized as binary (satisfactory or unsatisfactory) based on cut-off (mean scores) marks ( Table 1).…”
Section: Discussionmentioning
confidence: 99%